A small molecule iCDM-34 identified by in silico screening suppresses HBV DNA through activation of aryl hydrocarbon receptor - Furutani, Yutaka; Hirano, Yoshinori; Toguchi, Mariko; Higuchi, Shoko; Qin, Xian-Yang; Yanaka, Kaori; Sato-Shiozaki, Yumi; Takahashi, Nobuaki; Sakai, Marina; Kongpracha, Pornparn; Suzuki, Takehiro; Dohmae, Naoshi; et al. (Cell death discovery, 2023)
IFN-alpha have been reported to suppress hepatitis B virus (HBV) cccDNA via APOBEC3 cytidine deaminase activity through interferon signaling. To develop a novel anti-HBV drug for a functional cure, we performed in silico screening of the binding compounds fitting the steric structure of the IFN-alpha-binding pocket in IFNAR2. We identified 37 compounds and named them in silico c ccDNA modulator (iCDM)-1–37. We found that iCDM-34, a new small molecule with a pyrazole moiety, showed anti-HCV and anti-HBV activities. We measured the anti-HBV activity of iCDM-34 dependent on or independent of entecavir (ETV). iCDM-34 suppressed HBV DNA, pgRNA, HBsAg, and HBeAg, and also clearly exhibited additive inhibitory effects on the suppression of HBV DNA with ETV. We confirmed metabolic stability of iCDM-34 was stable in human liver microsomal fraction. Furthermore, anti-HBV activity in human hepatocyte-chimeric mice revealed that iCDM-34 was not effective as a single reagent, but when combined with ETV, it suppressed HBV DNA compared to ETV alone. Phosphoproteome and Western blotting analysis showed that iCDM-34 did not activate IFN-signaling. The transcriptome analysis of interferon-stimulated genes revealed no increase in expression, whereas downstream factors of aryl hydrocarbon receptor (AhR) showed increased levels of the expression. CDK1/2 and phospho-SAMHD1 levels decreased under iCDM-34 treatment. In addition, AhR knockdown inhibited anti-HCV activity of iCDM-34 in HCV replicon cells. These results suggest that iCDM-34 decreases the phosphorylation of SAMHD1 through CDK1/2, and suppresses HCV replicon RNA, HBV DNA, and pgRNA formation.